Analisis Gaya Kepemimpinan dan Manajemen di PT. Sejahtera Wahana Gemilang - Ade Rizaldi Hidayatullah; Ahmad Dhani Syahrudin; Mochammad Isa Anshori (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research aims to analyze the leadership and management styles applied at PT. Sejahtera Wahana Gemilang, a subsidiary of PT. Chitose International Tbk. which operates in the field of furniture distribution. Through a literature study, this research examines how transformational leadership style and participative management can influence company performance in meeting customer needs in the office, school, hotel, cafe and restaurant furniture sectors. The research results show that the combination of transformational leadership style and participative management is very important for the company's success in increasing innovation, employee motivation, customer satisfaction and competitiveness in the furniture industry.